Standar Operasional Prosedur Budi Daya Nanas sebagai Upaya Penanggulangan Serangan Hama dan Penyakit pada Tanaman Nanas - Siti Rodliyatun; Sinta Triyanti; Sugeng Heri Suseno; Widodo Widodo (Jurnal Pusat Inovasi Masyarakat (PIM), 2019)
Pineapple is one of the important commodities owned by Indonesia. There are so many pineapple producing areas in Indonesia, one of which is Sipahutar District. Sipahutar is a pineapple center in North Tapanuli, North Sumatra. The program of the Agro Creative Field Station (SLAK) aims to socialize and implement pineapple cultivation Standard Operational Procedure (SOP) as an effort to overcome pests and diseases in pineapple plants. Which starts from observing diseases in the field, processing and solarizing the soil, planting, training in making Plant Growth Promoting Rhizobacteria (PGPR), fertilizing, maintaining, until harvesting. Diseases found in the field are root rot disease caused by fungi Thielaviopsis paradoxa and pineapple wilt caused by the Pineapple Mealybug Wilt-associated Virus (PMWaV). Soil treatment makes the soil healthier because of the availability of organic material for the soil that comes from the provision of manure when processing the soil. Besides that, it is also able to prevent weed growth and minimize the use of herbicides. Whereas soil solarization can increase soil temperature so that it causes disease in the soil, nematodes, and dead weed seeds; increase the activity of some beneficial microbes in the soil; improve nutrition available to plants. Soils that were given a solarization treatment were darker in color compared to soils without solarization treatment. The use of healthy seeds and soaking seeds with PGPR before planting is an effort to restore soil and plants. However, the results are not yet visible, because the plant age is only 1 week when the SLAK program is complete.